Agent-based modeling of energy efficiency policies: Enhancing sustainable development and economic growth - Chuanzhi Huo; Muhammad Mohsin; Manal Alidarous (Energy Strategy Reviews)
This research examines how energy efficiency measures impact macroeconomic results and solves an important research deficiency. An analysis of how energy efficiency policies impact macroeconomic dynamics occurs through agent-based modeling (ABM). This research evaluates two approaches to sustainable economic development by studying tax incentives as indirect measures and public research laboratory R&D investments as direct measures. The implemented research and development-focused energy efficiency policies create superior environmental benefits while preserving economic stability, according to research results. The study demonstrates why carefully planned government policies are essential for sustainable ecological development and economic stability. The research data provides crucial knowledge for government officials who need practical guidance for merging energy efficiency strategies into economic planning systems. This research expands knowledge about energy efficiency relationships between the environment and the economy while offering directions for additional study on the multiple connections between energy use and economic stability and environmental objectives.